2005
DOI: 10.1007/bf02893060
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C—A novel marker of glomerular filtration rate: A review

Abstract: Glomerular filtration rate is routinely assessed by measuring the serum markers such as urea nitrogen and serum creatinine. Although these markers are widely used to assess renal function but they do not perform optimally in certain clinical settings. There is thus a practical need for an easily automated alternative to plasma creatinine, which would be more specific, sensitive and reliable from the analytical and clinical view point. Compared with the above endogenous markers, and time consuming laborious tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
10
0
2
Order By: Relevance
“…22,23 Several studies have shown that levels of serum cystatin-C are a more precise marker of GFR compared to serum creatinine levels, as cystatin-C increases earlier and higher than serum creatinine, with GFR decreases. 8 Cystatin-C is also not affected by obesity, height, gender, body composition, or age (except for under 1 year of age). 24 A study in Poland in 1999 found that lead-exposed children have glomerular and tubular renal dysfunction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…22,23 Several studies have shown that levels of serum cystatin-C are a more precise marker of GFR compared to serum creatinine levels, as cystatin-C increases earlier and higher than serum creatinine, with GFR decreases. 8 Cystatin-C is also not affected by obesity, height, gender, body composition, or age (except for under 1 year of age). 24 A study in Poland in 1999 found that lead-exposed children have glomerular and tubular renal dysfunction.…”
Section: Discussionmentioning
confidence: 96%
“…5 Many studies have shown serum cystatin-C levels to be a better indicator of GFR compared to serum creatinine levels, making it more sensitive as a marker for changes in renal function. [6][7][8][9] A previous study conducted in the District of North Minahasa Regency, Talawaan reported a mean blood lead level that exceeded the threshold of 25.8 μg/dL. The suspected source of pollution was a gold mine possibly affecting villages located downstream from a river along the transportation route for mineral processing.…”
mentioning
confidence: 98%
“…Sarkar et al [23] demonstrated that serum creatinine in their research work was a neither sensitive nor reliable biomarker for early identification of mild to moderate degrees of AKI. In addition, several previously published researches including Laterza et al [24], Le Bricon et al [25], Bianchi et al [26] and John et al [27] had concluded that serum cystatin C and beta2 microglobulin were easily applicable, highly sensitive indicators for AKI in their study when compared to routinely used serum creatinine.…”
Section: Discussionmentioning
confidence: 99%
“…Possui o ponto isoelétrico de 9,3, permanecendo assim positivamente carregada em todos os fluidos do corpo. (193)(194) Devido à essas características, a Cis-C é livremente filtrada pelo glomérulo, não é segregada, mas reabsorvida pelas células epiteliais tubular e em seguida catabolizada de modo que não retorna ao sangue. (192,194) Desta forma a Cis-C é utilizada como marcador da Doença Renal Crônica (DRC).…”
Section: Biossensor De Cis-cunclassified
“…(193)(194) Devido à essas características, a Cis-C é livremente filtrada pelo glomérulo, não é segregada, mas reabsorvida pelas células epiteliais tubular e em seguida catabolizada de modo que não retorna ao sangue. (192,194) Desta forma a Cis-C é utilizada como marcador da Doença Renal Crônica (DRC). Uma vantagem do seu uso como marcador, é que esta não varia em função da idade, sexo, massa muscular e etnia, o que garante uma maior precisão no diagnóstico.…”
Section: Biossensor De Cis-cunclassified